Preoperative Factors Predict Postoperative Trajectories of Pain and Disability Following Surgery for Degenerative Lumbar Spinal Stenosis. Issue 21 (1st November 2020) - Hébert, Jeffrey J.; Abraham, Edward; Wedderkopp, Niels; Bigney, Erin; Richardson, Eden; Darling, Mariah; Hall, Hamilton; Fisher, Charles G.; Rampersaud, Y. Raja; Thomas, Kenneth C.; Jacobs, W. Bradley; Johnson, Michael; et al.
Abstract : Study Design: Longitudinal analysis of prospectively collected data. Objective: Investigate potential predictors of poor outcome following surgery for degenerative lumbar spinal stenosis (LSS). Summary of Background Data: LSS is the most common reason for an older person to undergo spinal surgery, yet little information is available to inform patient selection. Methods: We recruited LSS surgical candidates from 13 orthopedic and neurological surgery centers. Potential outcome predictors included demographic, health, clinical, and surgery-related variables. Outcome measures were leg and back numeric pain rating scales and Oswestry disability index scores obtained before surgery and after 3, 12, and 24 postoperative months. We classified surgical outcomes based on trajectories of leg pain and a composite measure of overall outcome (leg pain, back pain, and disability). Results: Data from 529 patients (mean [SD] age = 66.5 [9.1] yrs; 46% female) were included. In total, 36.1% and 27.6% of patients were classified as experiencing a poor leg pain outcome and overall outcome, respectively. For both outcomes, patients receiving compensation or with depression/depression risk were more likely, and patients participating in regular exercise were less likely to have poor outcomes. Lower health-related quality of life, previous spine surgery, and preoperative anticonvulsant medication use were associated with poor leg pain outcome. Patients with ASA scores more than two, greater preoperative disability, and longer pain duration or surgical waits were more likely to have a poor overall outcome. Patients who received preoperative chiropractic or physiotherapy treatment were less likely to report a poor overall outcome. Multivariable models demonstrated poor-to acceptable (leg pain) and excellent (overall outcome) discrimination. Conclusion: Approximately one in three patients with LSS experience a poor clinical outcome consistent with surgical non-response. Demographic, health, and clinical factors were more predictive of clinical outcome than surgery-related factors. These predictors may assist surgeons with patient selection and inform shared decision-making for patients with symptomatic LSS. Level of Evidence: 2 Abstract : We investigated for potential predictors of outcome following degenerative lumbar spinal stenosis surgery. In this longitudinal study of 529 patients, approximately one in three patients experienced a poor clinical outcome. Demographic, health, and clinical factors were more predictive of clinical outcome than surgery-related factors.